Sosialisasi dan pelatihan pengisian spt pajak hotel kategori rumah kos di kampung dumpoh Kota Magelang - Agustina Prativi Nugraheni; Diah Agustina Prihastiwi; Octavia Lhaksmi Pramudyastuti (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2023)
The economic development in Magelang City is growing rapidly with the presence of Tidar University, especially in RW VII Kampung Dumpoh, Potrobangsan Village. This development can be seen especially in the increasing number of room rental businesses. The growing number of students living in Magelang, especially in Kampung Dumpoh, is driving the economic growth of the community. On the other hand, many owners of room rental businesses are not aware that they are obligated to collect and report taxes on room rentals. Knowledge about tax calculation and reporting is also lacking among the community. Based on this phenomenon, this Community Service Program aims to increase awareness and compliance of room rental business owners regarding the importance of reporting taxes through socialization and training. Additionally, this program will provide training on tax calculation, filling, and reporting of the tax for the room rental business